Efficacy and economics of plant extracts and biopesticides for the management of pea leaf miner - Sharma, S D Sharma; Sharma, S D; Sharma, S D (Indian Journal of Plant Protection, 2020)
Field experiments were carried out during two consecutive Rabi seasons of 2013-14 and 2014-15 to evaluate the efficacy of biopesticides like neemban (azadirachtin 0.15 % EC) @ 5ml/l and three plant extracts viz., extract of the mixture of leaves of 5 plant species (bhang, karvi, walnut, kaner and darek @ 1 kg each), aqueous root extract of sweet flag (Acorus calamus) @ 5.0% ,aqueous seed extract of darek (Melia azedarach) @ 5%, aqueous root extract of sweet flag @ 2.5% in comparison to a recommended insecticide malathion (Milthion 50 EC) @ 1ml/l as standard check. The findings revealed that malathion was the most effective and economical chemical against leaf miner attacking garden pea with the least leaf infestations of 6.3 per cent after 10 days of 2nd spray during both the years with the highest yield of 47.4 q/ha. But, in view of the safety to the human health and ecology, biopesticides like neemban (T3) and plant extracts like extract prepared from 5 plant species (T1) and used as 5% (bhang, karvi, walnut, kaner and darek) were also found to be effective with 13.6 and 19.2% leaf miner infestation after 10 days of their 2nd spray as compared to control (52.0%). The yield of garden pea was also significantly higher in these biopesticides and plant extract treatments with 42.1 and 40.8 q/ha as compared to control which recorded the yield of 27.4 q/ha